REFORMASI BIROKRASI: KORUPSI DALAM BIROKRASI INDONESIA - Hardiyanto Rahman (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2022)
Indonesian Government Bureaucratic Reform in Grand Design Bureaucratic Reform is expected to become a World Class Bureaucracy with bureaucratic reform agendas since 2010 and will be completed in 2024. This research is a research based on secondary data that utilizes various data and documents from various sources in the form of reports, research, books, journals and other data from the government and private parties through Google Scholar and the official government website. This study uses 3 main indicators, namely the Development of Corruption in Indonesia, Bureaucratic Reform Efforts and Challenges/Obstacles in Bureaucratic Reform. The results of the study show that the Indonesian government's bureaucratic reform has changed for the better, but at the local government level it still needs to be a major concern because in addition to the high level of corruption, the index of bureaucratic reform in local governments is still quite low.